SUCCESSFUL TRANSITION CARE FOR ADOLESCENT AND YOUNG ADULTS WITH DIABETES: A SINGLE-CENTRE EXPERIENCE AND REPORT - Lee, Qiao Yun; Ambak, Noor Azleen; Tan, Alexander Tong Boon; Ibrahim, Luqman; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Planned and coordinated transition to adult services should be provided in all centres managing adolescents with diabetes. A variety of transition intervention programs can be implemented to ensure higher clinic attendance and lower disengagement rates. This audit aims to identify success in a single-centre transition clinic amongst adolescents with diabetes mellitus (DM). METHODOLOGY All adolescents transferred between January 2017-December 2022 were included in the analysis. Patients were either transferred out or referred to the transition clinic in the same centre. They were monitored for at least 2 years before transferring to the general adult diabetes clinic. Success transfer rate is defined as being seen at least twice in the first year. Success transition care is defined when the patient completed 2 years follow-up. Pre- and post-transfer HbA1c were compared. RESULT A total of 47 patients were transferred during the study period. Thirteen patients requested to be transferred to a different hospital. Two were enrolled in a local research project. Four patients were planned for transition care but did not turn up. Of the 28 patients who presented to the transition clinic, 71% (n=20) were Type 1 DM and 29% (n=8) were Type 2 DM. Twelve (43%) were female and their median age at transfer was 19.2 ± 2.2 years old. The success transfer rate was 100% and successful transition care was 77% (n=23). Five patients requested to be transferred due to either studying/ working elsewhere (n=3) and the remaining 2 had financial constraints. There were no differences in the pre- and post-transfer A1c. Median pretransfer A1c was 9.07 ± 2.33% and median post transfer A1c was 9 ± 2.4% respectively. CONCLUSION Preparing the idea of transition early, collaboration between the paediatric and adult services within the same centre and identifying point persons in the service helped with the outcome and success rate of transition services in this centre.